Edukasi keluarga berencana dan metode kontrasepsi pada wanita usia subur di Kecamatan Kemuning, Palembang, Sumatera Selatan - Ratika Febriani; Ratih Pratiwi; Indri Ramayanti; Putri Aprilia Kusuma Widyanti (Fakultas Kedokteran Universitas Sriwijaya, 2025)
The Family Planning Program (KB) is a program that aims to control the rate of population increase, regulate pregnancy, distance, and the ideal age for childbirth. In Indonesia, the coverage of active family planning participants in long-term methods is still relatively low, namely: AKDR (7.4%), AKBK (7.4%), MOW (2.7%), and MOP (0.5%) which is still far below the target of the National Medium-Term Development Plan (RPJMN) of 66%. Many factors cause contraceptive users, one of which is the knowledge of family planning users about contraceptive methods. Therefore, it is necessary to educate the community to increase understanding, especially in women of childbearing age, about family planning and various contraceptive methods, so that they can choose and use appropriate methods to support reproductive health and family welfare. Community service activities are carried out by providing education through material presentations with lecture and discussion methods. Before and after the provision of education, the level of community knowledge about family planning and contraceptive methods was measured. The average pretest score was 53.17 and the average post test score was 87.34. This shows that there is an increase in participants' knowledge about the concept of family planning and various contraceptive methods.